2005
DOI: 10.1073/pnas.0507413102
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax : Recent world expansion and genetic identity to Plasmodium simium

Abstract: Plasmodium vivax causes the most geographically widespread human malaria, accounting annually for 70 -80 million clinical cases throughout the tropical and subtropical regions of the world's continents. We have analyzed the DNA sequences of the Csp (circumsporozoite protein) gene in 24 geographically representative strains of P. vivax and 2 of P. simium, which parasitizes several species of New World monkeys. The Csp sequences are of two types, VK210 and VK247, which differ by three diagnostic amino acid repla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 36 publications
6
56
0
1
Order By: Relevance
“…S5). The CR region varies in the number of amino acid motifs, and there is also sequence variation among the oligopeptides (19). Between the 3′ NR and the CR regions, there is an insertion region (IR) of relatively simple structure (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S5). The CR region varies in the number of amino acid motifs, and there is also sequence variation among the oligopeptides (19). Between the 3′ NR and the CR regions, there is an insertion region (IR) of relatively simple structure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the nature of the repeated amino acid motifs in the CR region, human isolates are of two types, VK 210 and VK 247, distinguished by several diagnostic SNPs in the 5′, 3′, and IR regions (19). In great apes, all isolates displayed SNPs and motifs related to the VK 247 Csp type in human P. vivax (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence has shown that both species of malaria are significantly less diverse than primate malarias and likely have undergone genetic bottlenecks associated with host switching and emergence out of Africa, likely less than 10,000 y ago (63,(68)(69)(70)(71)(72). As these species have emerged from the bottleneck, they likely have undergone both sustained and recent selection.…”
Section: Discussionmentioning
confidence: 99%
“…However, markedly divergent sequence variants were found in isolates from China and North Korea (Mann et al 1994). Although VK210 and VK247-type sequences often occur in sympatric parasite populations, there are no examples of a hybrid repeat array with both repeat types (Lim et al 2005).…”
Section: Abstract: Malaria -Plasmodium Vivax -Genetic Markers -Genetmentioning
confidence: 99%
“…However, markedly divergent sequence variants were found in isolates from China and North Korea (Mann et al 1994). Although VK210 and VK247-type sequences often occur in sympatric parasite populations, there are no examples of a hybrid repeat array with both repeat types (Lim et al 2005).A third type of repeat unit [APGANQ(E/G)GAA], identical to that described for Plasmodium simiovale, characterises the so-called P. vivax-like parasites (Qari et al 1993a). Although P. vivax-like CSP repeats have been found in parasite isolates across the world, its global distribution remains unconfirmed (Gopinath et al 1994).…”
mentioning
confidence: 99%